Potential Distribution of Chagas Disease Vectors (Hemiptera, Reduviidae, Triatominae) in Colombia, Based on Ecological Niche Modeling - Gabriel Parra-Henao; Laura C. Suárez-Escudero; Sebastián González-Caro (Journal of Tropical Medicine)
Ecological niche modeling of Triatominae bugs allow us to establish the local risk of transmission of the parasite Trypanosoma cruzi, which causes Chagas disease. This information could help to guide health authority recommendations on infection monitoring, prevention, and control. In this study, we estimated the geographic distribution of triatomine species in Colombia and identified the relationship between landscape structure and climatic factors influencing their occurrence. A total of 2451 records of 4 triatomine species (Panstrongylus geniculatus, Rhodnius pallescens, R. prolixus, and Triatoma maculata) were analyzed. The variables that provided more information to explain the ecologic niche of these vectors were related to precipitation, altitude, and temperature. We found that the species with the broadest potential geographic distribution were P. geniculatus, R. pallescens, and R. prolixus. In general, the models predicted the highest occurrence probability of these vectors in the eastern slope of the Eastern Cordillera, the southern region of the Magdalena valley, and the Sierra Nevada of Santa Marta.